2021
DOI: 10.1002/ep.13686
|View full text |Cite
|
Sign up to set email alerts
|

Distributed wind and solar power for grid sustainability and emission reduction

Abstract: This article intends to maximize the amount of solar and wind power produced while minimizing the tested network's annual energy loss. It also wants to improve the voltage profile and reduce the dependence on the upstream network. Two types of distributed generation sources, that is, wind DGs and solar DGs, are investigated. In this article, the network loads vary according to the local consumption pattern. This research shows that the optimal utilizing of solar and wind distributed generation sources causes e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
(45 reference statements)
1
6
0
Order By: Relevance
“…On the other hand, the relationship collapses when globalization is coupled with nonrenewable energy sources. Several other studies have corroborated the correlation between wind and solar energy demand and the capping of carbon emissions [56][57][58][59]. The results further revealed that increased coal and brown coal consumption increases carbon intensity worldwide.…”
Section: Resultssupporting
confidence: 53%
“…On the other hand, the relationship collapses when globalization is coupled with nonrenewable energy sources. Several other studies have corroborated the correlation between wind and solar energy demand and the capping of carbon emissions [56][57][58][59]. The results further revealed that increased coal and brown coal consumption increases carbon intensity worldwide.…”
Section: Resultssupporting
confidence: 53%
“…Weibull distribution is a suitable model for determining the frequency distribution in the studied locations. It is defined by the following equation [10][11][12]:…”
Section: Wind Characteristicmentioning
confidence: 99%
“…So, it is predicted that the demands and installations of grid‐connected distributed generation (DG) systems will increase rapidly 7–10 . The distributed photovoltaic energy system reduce reliance on upstream distribution systems, annual energy losses and carbon dioxide emission 11 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The distributed photovoltaic energy system reduce reliance on upstream distribution systems, annual energy losses and carbon dioxide emission. 11 Electrical distribution system (EDS) can manage and meet the rising demand of load by integration of distributed energy generation resources. [12][13] Distributed generation resources like photovoltaic system and electric load are integrated with the energy storage system (ESS) in the EDS.…”
mentioning
confidence: 99%